2022
DOI: 10.3390/ijms23126435
|View full text |Cite
|
Sign up to set email alerts
|

A NAC Transcription Factor from ‘Sea Rice 86′ Enhances Salt Tolerance by Promoting Hydrogen Sulfide Production in Rice Seedlings

Abstract: Soil salinity severely threatens plant growth and crop performance. Hydrogen sulfide (H2S), a plant signal molecule, has been implicated in the regulation of plant responses to salinity stress. However, it is unclear how the transcriptional network regulates H2S biosynthesis during salt stress response. In this study, we identify a rice NAC (NAM, ATAF and CUC) transcription factor, OsNAC35-like (OsNACL35), from a salt-tolerant cultivar ‘Sea Rice 86′ (SR86) and further show that it may have improved salt tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…The homogenates were centrifuged at 12,000× g for 20 min at 4 • C, and the resulting supernatants were used for assays for SOD, POD, and CAT activities. SOD, POD, and CAT activities were measured as previously described [37]. All spectrophotometric values are measured via spectrophotometer (Persee TU-1810, Zhengzhou, China).…”
Section: Assays For Antioxidant Enzymes Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The homogenates were centrifuged at 12,000× g for 20 min at 4 • C, and the resulting supernatants were used for assays for SOD, POD, and CAT activities. SOD, POD, and CAT activities were measured as previously described [37]. All spectrophotometric values are measured via spectrophotometer (Persee TU-1810, Zhengzhou, China).…”
Section: Assays For Antioxidant Enzymes Activitymentioning
confidence: 99%
“…The total chlorophyll contents were measured as described previously [37]. In brief, the rosette leaves from each genotype were cut into sections, flash-frozen with liquid nitrogen, and then stored at −80 • C before used.…”
Section: Physiological and Biochemical Measurementsmentioning
confidence: 99%
“…Studies concerning free radical damage reactions in plant have revealed that reactive oxygen species (ROS) have diverse functions in various developmental and physiological processes, including seed germination, root morphogenesis, stomatal movement, leaf development, and abiotic stress responses [4,18,[26][27][28]. It has been reported that respiratory burst oxidase homologs (Rbohs), as homologs of mammalian NADPH oxidases, participate in accumulation of apoplastic ROS (e.g., O 2 − and H 2 O 2 ), which are targeted to the plasma membrane [29].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicated that the research on sea rice mainly focused on planting, the saline‐alkali tolerance principle, yield improvement, and soil modification (Chen et al, 2017 ; Xie et al, 2021 ). The root system of ‘Haidao 86’ was promoted in low‐salt seawater (3‰), the optimum salinity for seed germination was 3‰, and the maximum salinity tolerance reached 15‰ (Sun et al, 2022 ). Experiments in Xinjiang, Heilongjiang, Guangdong, and other places were successful, among which the unit yield of sea rice in the Xinjiang Kashi saline‐alkali soil experimental field reached 8.24 tons/ha (Wang et al, 2019 ), and the unit yield of sea rice in the Qingdao saline‐alkali soil experimental field reached 10.38 tons/ha (Zhang, 2018 , 2022 ).…”
Section: Introductionmentioning
confidence: 99%